Motivic System in B. Kanapyanov’s Lyrical Works: A Study of Poetic Language and Cultural Synthesis - Dulatkyzy, Moldir Amangeldi; Kadisha, Nurgali; Nurmanova, Zhanna; Nurgali , Rabiga (Journal of Ecohumanism, 2024)
This article explores the motivic system in the lyrical works of Kazakh poet B. Kanapyanov, focusing on the content and structural components of his poetic language. The study aims to describe stable motives through their creation and development in Kanapyanov’s poetry, considering both literal and figurative expressions. The authors compare Kanapyanov’s motives with general cultural motives, classifying the ways and means of their representation in his literary texts. Special attention is given to the image of the steppe, which is filled with national-specific semantic associations. Kanapyanov’s poetry is characterized by genre synthesis, combining strategies from epistolary writing, documentary prose, elegy, philosophical ode, high book style, romantic nostalgia, social pathos, and piercing confession. His poetic heritage includes various genre varieties that allow him to express his worldview fully. Kanapyanov’s lyrics are influenced by both nomadic thinking and Russian futurism, with the rhythmic structure of syllabics from Kazakh versification and the clarity and poster-like accent verse from Russian futurism. The categories of memory and conscience serve as ethical assessments of time in his works, while the repeated images of a child, sleep, paths, souls, birds, horses, flocks, mares, and dombra are explained by ethnic stereotypes that create a sense of the author’s involvement in his native culture. Folklore and mythological symbolism play a defining role in expressing the national picture of the world and ideological dominants that determine the lyrical hero’s dialogue with the world. Kanapyanov’s bilingualism and commitment to syllabics as an aesthetic strategy for expressing the national worldview have led to the creation of the "Vekzametry" concept, a collection showcasing his poetic experimentation with ancient, classical forms of versification to reveal his sense of modernity.